Establishment of a Novel Mouse Hepatocellular Carcinoma Model for Dynamic Monitoring of Tumor Development by Bioluminescence Imaging - Cao, Xiangyi; Zhang, Yulong; Zhou, Qianqian; Sun, Sujing; He, Minwei; Wang, Xiaohui; Ma, Ping; Yang, Xiaoang; Lv, Liping; Zhan, Linsheng (Frontiers in Oncology, 2022)
In this study, a novel mouse model of hepatocellular carcinoma (HCC) was established by simultaneously knocking out Pten and p53 suppressor genes and overexpressing c-Met and △90-β-catenin proto-oncogenes in the livers of mice via hydrodynamic injection (HDI). The mutations were introduced using the CRISPR/Cas9 and Sleeping Beauty transposon systems. In this way, a primary liver cancer model was established within six weeks. In addition, macrophages expressing arginase-1(Arg1) promoter coupled with firefly luciferase were engineered for bioluminescence imaging (BLI) of the tumor microenvironment. This novel, rapidly-generated model of primary hepatocellular carcinoma can be monitored noninvasively, which can facilitate not only applications of the model, but also the development of new drugs and treatment strategies of HCC.